Nuocytes from mesenteric lymph node promote allergic responses in a mouse model - Lin,Lin (2021)
Abstract Introduction: Nuocytes play an important role in Type 2 immunity. However, the contribution of ILC2s to allergic rhinitis remains to be clearly elucidated. Objective: To evaluate the role of nuocytes from mesenteric lymph node on allergic responses in mice. Methods: After intraperitoneal administration of interleukin IL-25 and IL-33 to wild-type and Il17br-/-Il1rl1-/- double-deficient mice, nuocytes were purified from the the nasal-associated lymphoid tissue and mesenteric lymph nodes. Then, we assessed productions of IL-5 and IL-13 in nuocytes’ cultures. Finally, we adoptively transferred the mesenteric lymph node-derived nuocytes from wild-type and Il17br-/-Il1rl1-/- mice to the murine model of allergic rhinitis to evaluate their roles in nasal allergic responses. Results: We showed that nuocytes in the mesenteric lymph nodes of wild-type mice were upregulated after application of IL-25 and IL-33, and were induced to produce IL-5 and IL-13. Numbers of sneezing and nasal rubbing as well as eosinophils were all enhanced after the adoptive transfer of wild-type nuocytes. Concentrations of IL-5, IL-13, IL-25 and IL-33 in nasal lavage fluid of allergic mice were also increased. However, nuocytes fromIl17br-/-Il1rl1-/- mice did not increase sneezing and nasal rubbing and eosinophilia, and upregulate the above cytokines in the nasal lavage fluid. Conclusion: The findings demonstrate that nuocytes from the mesenteric lymph nodes of wildtype mice promote allergic responses in a mouse model.